Driving with Pets as a Risk Factor for Motor Vehicle Collisions among Older Drivers - Blunck, Hallie (Accid Anal Prev, 2013)
Increasing rates of distraction-related motor vehicle collisions (MVCs) continue to raise concerns regarding driving safety. This study sought to evaluate a novel driving-related distraction, driving with a pet, as a risk factor for MVCs among older, community dwelling adults. Two thousand licensed drivers aged 70 and older were identified, of whom 691 reported pet ownership. Comparing pet owners who did and did not drive with their pets, neither overall MVC rates (rate ratio [RR] 0.97 95% confidence interval [CI] 0.75–1.26) nor at-fault MVC rates (RR 0.84 95% CI 0.57–1.24) were elevated. However, those who reported always driving with a pet in the vehicle had an elevated MVC rate (RR 1.89 95% CI 1.10–3.25), as compared to those who did not drive with a pet. The MVC rate was not increased for those reporting only sometimes or rarely driving with a pet in the vehicle. The current study demonstrates an increased risk of MVC involvement in those older drivers who always take a pet with them when they drive a vehicle. When confronted with an increased cognitive or physical workload while driving, elderly drivers in prior studies have exhibited slower cognitive performance and delayed response times in comparison to younger age groups. Further study of pet-related distracted driving behaviors among older drivers as well as younger populations with respect to driver safety and performance is warranted to appropriately inform the need for policy regulation on this issue.